2017
DOI: 10.1107/s2053229616018751
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-forced dimerization of copper(I)–olefin complexes bearing a 1,3,4-thiadiazole core

Abstract: As an important class of heterocyclic compounds, 1,3,4-thiadiazoles have a broad range of potential applications in medicine, agriculture and materials chemistry, and were found to be excellent precursors for the crystal engineering of organometallic materials. The coordinating behaviour of allyl derivatives of 1,3,4-thiadiazoles with respect to transition metal ions has been little studied. Five new crystalline copper(I) π-complexes have been obtained by means of an alternating current electrochemical techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
0
9
0
5
Order By: Relevance
“…In our previous works we have shown an impact of a weak interactions, including hydrogen bonding, on the structural organization in π-complex compounds. [28][29][30] The weakening of the Cu-O interaction in 2 (and the strengthening of Cu-S as a result) can be explained by the fact, that the anion in 2 is involved in a larger number of the H-bonding, due to the presence of the water molecule, all of which competes with the Cu-O interaction. Finally, since the water was presented in both reaction mixtures, but co-crystallized only in 2, its presence in its crystal structure should be explained by the different character of benzene-and p-toluenesulfonate anions.…”
Section: Atoms Involved Distances å Angle Deg D−h•••a D•••h D•••h D•••h D−h•••mentioning
confidence: 99%
“…In our previous works we have shown an impact of a weak interactions, including hydrogen bonding, on the structural organization in π-complex compounds. [28][29][30] The weakening of the Cu-O interaction in 2 (and the strengthening of Cu-S as a result) can be explained by the fact, that the anion in 2 is involved in a larger number of the H-bonding, due to the presence of the water molecule, all of which competes with the Cu-O interaction. Finally, since the water was presented in both reaction mixtures, but co-crystallized only in 2, its presence in its crystal structure should be explained by the different character of benzene-and p-toluenesulfonate anions.…”
Section: Atoms Involved Distances å Angle Deg D−h•••a D•••h D•••h D•••h D−h•••mentioning
confidence: 99%
“…Похідні 1,3,4-тіадіазолів володіють широким спектром фармакологічних властивостей (антибактеріальною, протигрибковою, протитуберкульозною, протизапальною, анальгетичною тощо), їх використовують для створення матеріалів з важливими оптичними, магнітним та люмінесцентними властивостями, а також застосовують у кристалічній інженерії різноманітних металокомплексів [1][2][3][4][5][6][7]. Незважаючи на те, що комплексоутворення іонів d-металів з лігандами, що містять у своєму складі тіадіазольне ядро, інтенсивно досліджувалось впродовж декількох десятиліть, сьогодні відомо лише близько тридцяти структурно вивчених π-координаційних сполук на основі алільних похідних 1,3,4-тіадіазолів.…”
Section: вступunclassified
“…Their diverse biological activity possibly arises from the presence of the NCS moiety in the molecule (Oruç et al, 2004). An interesting feature of the metal-ligand chemistry of these compounds is that the complexes can be either mononuclear (Tzeng et al, 2004;Varna et al, 2018;Qiu et al, 2014) or binuclear (Deckert et al, 2016;Ardan et al, 2017). A search of the Cambridge Structural Database (CSD Version 5.4, update of February 2019; Groom et al, 2016) revealed that although crystal structures have been reported for complexes of either 1,3,4-thiadiazole derivatives or OAc with a number of metal ions, including zinc, copper, nickel, manganese, cadmium, cobalt and palladium, no examples are known of mixed-ligand metal complexes containing both 1,3,4-thiadiazole derivatives and OAc.…”
Section: Chemical Contextmentioning
confidence: 99%